Fostering Socio-Economic Development in Ghana through Entrepreneurship and Innovation - Essuman, Bismark (My University, 2022)
The ongoing development problems on the continents, from Africa to Asia, have drawn attention from around the world on numerous occasions in the first few years of the twenty-first century. The gap between industrialized nations and emerging economies is getting wider as government initiatives to support innovation and entrepreneurship become more widespread in those nations. For developing nations, entrepreneurship and innovation have significant potential advantages. To that end, the majority of Sub-Saharan African nations support the growth of small and medium-sized enterprises (SMEs) as a way to reduce poverty, provide jobs, and advance national economic development.
Keywords: Economic Development and Growth; Social Growth; Innovation & Creativity